Ecological Assessment of Seagrass Meadows in Liukang Loe Island, South Sulawesi Using Seagrass Ecological Quality Index (SEQI) - Adelia Almira; Rohani Ambo-Rappe; Widyastuti Umar; Suci Rahmadani Artika; St. Firjatih Widhah (International Journal of Agriculture System, 2026)
Seagrass meadows on Liukang Loe Island, Bulukumba Regency, provide essential coastal ecological functions but are increasingly exposed to tourism and local maritime activity. This study aimed to assess the health of seagrass ecosystems using the Seagrass Ecological Quality Index (SEQI). The results showed that the two study stations had SEQI values of 0.84 and 0.85, indicating that the ecological status of the seagrass meadows ranged from Good to Very Good. These high index values were supported by the presence of nine seagrass species, an average seagrass cover of 35.48%, and 100% water clarity, all of which indicate favorable habitat conditions for fish. Therefore, integrated and sustainable coastal management strategies should be implemented to mitigate the impacts of human activities and ensure the long-term conservation of the ecological functions of seagrass meadows.